2002
DOI: 10.1291/hypres.25.717
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Hypertension Management in Japan in 2000.

Abstract: To evaluate the current status of the management of hypertensive patients in Japan, we investigated 907 treated hypertensive patients (486 females and 421 males; mean age, 66.7 years) followed by cardiologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 39 publications
2
28
2
Order By: Relevance
“…Although the percentage of patients using diuretics in the present study was higher than that found in previous reports from Japan (3)(4)(5), the prescription rate of diuretics (8.6%) among patients with a history of stroke still seems to be low. In the Perindopril Protection against Recurrent Stroke study (PROGRESS), it was shown that combination therapy with an ACE-inhibitor (perindopril) and a diuretic (indapamide) appeared to reduce the risk of stroke (8).…”
Section: Number Of Diuretic Prescriptions (N)contrasting
confidence: 91%
See 2 more Smart Citations
“…Although the percentage of patients using diuretics in the present study was higher than that found in previous reports from Japan (3)(4)(5), the prescription rate of diuretics (8.6%) among patients with a history of stroke still seems to be low. In the Perindopril Protection against Recurrent Stroke study (PROGRESS), it was shown that combination therapy with an ACE-inhibitor (perindopril) and a diuretic (indapamide) appeared to reduce the risk of stroke (8).…”
Section: Number Of Diuretic Prescriptions (N)contrasting
confidence: 91%
“…The percentage of patients using diuretics (9.3%) in the J-HOME study was higher than that (4.0-5.4%) found in previous studies (3)(4)(5), but was similar to that found (12.6%) in another recent study (6). This trend could be attributable to the impact of recently published, large-scale intervention trials, such as the ALLHAT study, which emphasized the clinical significance of diuretics (1,16,17).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…A lack of data regarding the use of antihyperuricemic medications might have led to underestimation of the prevalence of hyperuricemia. Because the frequency of diuretics used as antihypertensives is low in Japan, 38 the influence of diuretics on our results was most likely small. Third, information on menopause was not available for our female subjects.…”
Section: Discussionmentioning
confidence: 92%
“…Thus, after taking into account the results of the Kyushu Lipid Intervention Study (KLIS) (15), the pravastatin anti-atherosclerotic trial in the elderly (PATE) (16), and the Japan Lipid Intervention Trial (J-LIT) (17), the Japan Atherosclerosis Society (JAS) Guidelines for Diagnosis and Treatment of Atherosclerotic Cardiovascular Diseases-which included new lipid management goalswere published in July 2002. Recently, we reported the current status of blood pressure management in hypertensive patients in Japan (18), and in this report, we have assessed the status of lipid management in the same population. The aim of this study was to clarify the current status of lipid management of hypertensive patients and to identify problems that warrant improvement.…”
Section: Introductionmentioning
confidence: 99%